Isolation of Drought-Resistance Gene Encoded GmNAC-D in Dering-1 Variety of Soybean - Prasetyo, Frengky Hermawan Hadi; Wibisono, Yossi; Ermawati, Netty (AGRIUM: Jurnal Ilmu Pertanian, 2025)
Drought is one of the most critical abiotic stresses limiting crop growth and productivity, causing substantial yield losses in major crops such as soybean (Glycine max L.). The No Apical Meristem (NAC) transcription factors (TFs) are plant-specific proteins that have been widely reported to play key roles in enhancing drought tolerance across various plant species. This study aimed to isolate and characterize a soybean NAC gene through a molecular approach. A NAC family gene was successfully isolated from drought-tolerant soybean cultivar Dering-1 and designated GmNAC-D (D = Dering-1). The gene was amplified by PCR-based cloning, sequenced and analyzed through bioinformatics, while tissue-specific expression was assessed using RT-PCR. The gene consists of a 762 bp open reading frame encoding 253 amino acids. Database analysis revealed that GmNAC-D shares high homology with GmNAC02, a known stress-responsive gene in soybean. Expression analysis across different tissues demonstrated that GmNAC-D is most abundantly expressed in stem tissue, followed by flowers and roots. Amino acid sequence analysis further confirmed its high similarity to GmNAC02, although with distinct expression profiles. The differential expression patterns of GmNAC genes suggest functional diversification during plant growth and development. Collectively, these findings expand the repertoire of soybean NAC transcription factors and provide a valuable genetic resource for the development of transgenic soybean with enhanced drought tolerance.